Estudo do efeito dos tratamentos duplex de nitrocementação e deposição de filmes DLC dopados com nitrogênio e silício nas propriedades tribológicas do aço M2 - Danelon, Miguel Rubira (2023)
DLC films have been the focus of recent research due to chemical inertia, low friction coefficient, high hardness, and interesting optical properties. But due to its problem of poor adhesion on metallic substrates, some alternatives have been developed to solve that problem, for example, the doping of DLC films like N and Si, and duplex treatments together with DLC film. Ionic plasma nitrocarburizing is a thermochemical treatment that improves the wear, fatigue, and corrosion properties, due to an iron nitride and carbonitrides formed on the surface and the nitrogen and the formation of a diffusion zone due to the carbon diffusion on the material. This work aims to study the effect of duplex treatment (nitrocarburizing+DLC) of silicon-doped and nitrogen-doped DLC on the wear resistance of AISI M2 in comparison with nitriding, nitrocarburizing, DLC, DLCN, and DLC-Si treated individually tribological behavior. Plasma treatments were carried out using a pulsed-DC power supply. Treatments were initialized, it was performed a plasma ablation cleaning with a gas mixture of 80%Ar-20%H2 for 1h. After the ablation treatments, plasma nitrocarburizing was performed with a gas mixture of 80%N2-15%H2-5%CH4 at 450ºC, a gas flow of 750sccm for 6h. By means of comparison, a nitriding treatment was performed under the same conditions but with a gas mixture of 80%N2-20%H2. DLC, DLCN, and DLC-Si films were deposited with a gas mixture of 90%CH4-10%Ar, 70%CH4-30%N2, and 90%CH4-8%Ar-2%HMDSO respectively, with a gas flow of 30sccm. All films were deposited for 2h. Duplex treatments were a combination of nitrocarburizing and DLC films with different doping. Duplex treatment with DLC-Si film was deposited in milling tools, to evaluate the effect of the treatment during the milling of aluminum alloy. Nitrocarburizing has presented a compound layer with thinner thickness when compared to nitriding treatment. So as the silicon and nitrogen-doped DLC films presented lower thickness in relation to conventional DLC film. Duplex treatments have shown a reduction of the compound layer and the DLC films when compared to simple treatments. Nitrocarburizing treatment has also presented a harder compound layer when compared to nitriding layer, due to the presence of the carbon element during treatment. DLC-Si film has shown the higher hardness among the DLC and DLCN treatments, due to the stabilization of sp3 hybridizations. While, the duplex treatments, has shown the highest hardness when compared to simple treatments, proving the efficiency of these treatments when compared to the simple ones. Duplex treatment of nitrocarburizing and DLC film doped with silicon presented the best wear resistance compared to other treatments, due to the stabilization of sp3 bonds in the film, which brings the film more hardness and thermal stability, the improve it is also due to the synergy between the compound layer and the DLC-Si film, which improves the wear resistance of the material, and, improves the adhesion of the film on the substrate. When milling aluminum, the treatment reduced the build-up edge formation without reducing the roughness of the milled sample. Thus, it is possible to conclude that the duplex treatment with nitrocarburizing and DLC film doped with silicon has presented the best performance during wear tests and has created the possibility of improving the useful life of AISI M2 milling tools.